Input specificity and labor's bargaining power: A production tree approach to functional income distribution - Lasare Samartzidis; Philipp Mundt; Jan Schulz-Gebhard (Bamberg University, Bamberg Economic Research Group (BERG), 2024)
This article examines how input relationships in fragmented production systems shape functional income inequality. We argue that input specificity - reflecting the degree of specialization in intermediate goods production - affects workers' bargaining power and, consequently, the labor share through skill premia and the disruptive potential of strikes. Using regional input-output data for European economies and a novel methodology for constructing sectoral production trees, we measure input specificity and analyze its impact on the functional income distribution. Our results suggest significant regional and sectoral differences in input specificity and reveal a robust positive association between input specificity and labor share, offering new insights into regional economic inequality.
Keywords: 330